2021
DOI: 10.3389/fvets.2021.704399
|View full text |Cite
|
Sign up to set email alerts
|

Ornithodoros puertoricensis (Ixodida: Argasidae) Associated With Domestic Fowl in Rural Dwellings From Córdoba Department, Caribbean Colombia

Abstract: Ticks of genus Ornithodoros are nidicolous parasites associated with a wide array of vertebrates. In humans, their bites cause hypersensitivity reactions and are capable to transmit pathogens of health concern. In the department of Córdoba, Caribbean region of Colombia, the first report of an Ornithodoros soft tick was made in 1980 by Betancourt, who described the collection of Ornithodoros talaje in human dwellings. Nevertheless, current the records of O. talaje made in South America have been questioned and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…Some species distributed in Colombia such as O. rudis have been related to recurrent fevers in the 20th century (Franco et al 1911 ; Pino Pou 1984 ; Faccini-Martínez and Botero-García 2016 ) but the old and rare reports of Ornithodoros spp. require taxonomic confirmation (López et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some species distributed in Colombia such as O. rudis have been related to recurrent fevers in the 20th century (Franco et al 1911 ; Pino Pou 1984 ; Faccini-Martínez and Botero-García 2016 ) but the old and rare reports of Ornithodoros spp. require taxonomic confirmation (López et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since the two infested hosts were recovered in urban areas of the state of Veracruz, it is necessary to monitor burrows and human settlements to identify whether ticks may be feeding on humans, as has been previously shown in Panama and Colombia (Bermúdez et al, 2017; López et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is essential to continue with studies that confirm the effective mechanism of transmission to ticks of a pathogen confirmed to date as exclusively transmitted by fleas (Blanton et al, 2016). Since the two infested hosts were recovered in urban areas of the state of Veracruz, it is necessary to monitor burrows and human settlements to identify whether ticks may be feeding on humans, as has been previously shown in Panama and Colombia (Bermúdez et al, 2017;L opez et al, 2021).…”
Section: O Puertoricensis (At This Moment)mentioning
confidence: 89%
“…All sequences were compared with GenBank reference sequences. A 99.51% identity percentage was obtained for O. puertoricensis MZ005590.1 and MZ005589.1 (López et al 2021) with the 16S rRNA sequence. For the CO1 sequence, an identity of 82.55% was obtained with the species Ornithodoros spheniscus MN027573.1 (Muñoz-García et al 2019), this is due to the fact that in GenBank there are no records of sequences of this gene for O. puertoricensis.…”
mentioning
confidence: 89%